2004
DOI: 10.1901/jaba.2004.37-171
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Effects of Extinction on Attention‐maintained Behavior Through Noncontingent Delivery of Attention or Stimuli Identified via a Competing Stimulus Assessment

Abstract: Recent research has shown that the noncontingent delivery of competing stimuli can effectively reduce rates of destructive behavior maintained by social-positive reinforcement, even when the contingency for destructive behavior remains intact. It may be useful, therefore, to have a systematic means for predicting which reinforcers do and do not compete successfully with the reinforcer that is maintaining destructive behavior. In the present study, we conducted a brief competing stimulus assessment in which non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 26 publications
2
50
0
Order By: Relevance
“…That is, the functional reinforcers for problem behavior (attention for Stephen and Matt and video games for James) were delivered contingent on problem behavior while the participant had the test stimulus and could obtain the reinforcement it produced concurrently. To date, only two other published studies have described the use of this type of assessment (Fisher et al, 2004;Fisher, O'Connor, Kurtz, DeLeon, & Gotjen, 2000). In those studies, Fisher and colleagues delivered attention contingent on problem behavior during the competing stimulus assessment after having determined that problem behavior was attention maintained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, the functional reinforcers for problem behavior (attention for Stephen and Matt and video games for James) were delivered contingent on problem behavior while the participant had the test stimulus and could obtain the reinforcement it produced concurrently. To date, only two other published studies have described the use of this type of assessment (Fisher et al, 2004;Fisher, O'Connor, Kurtz, DeLeon, & Gotjen, 2000). In those studies, Fisher and colleagues delivered attention contingent on problem behavior during the competing stimulus assessment after having determined that problem behavior was attention maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures used to examine the degree to which access to various stimuli displace problem behavior, relative to a nostimulus control condition, have recently been termed competing stimulus assessments (DeLeon, Rodriguez-Catter, Fisher, Delia, & Marhefka, 2000;Fisher, DeLeon, Rodriguez-Catter, & Keeney, 2004;Long, Hagopian, DeLeon, Marhefka, & Resau, in press). Several studies have demonstrated that noncontingent access to competing stimuli can effectively reduce problem behavior maintained by automatic reinforcement (Piazza, Fisher, Hanley, Hilker, & Derby, 1996;Ringdahl, Vollmer, Marcus, & Roane, 1997;Roane, Vollmer, Ringdahl, & Marcus, 1998;Shore, Iwata, DeLeon, Kahng, & Smith, 1997;Zhou, Goff, & Iwata, 2000).…”
Section: ____________________________________________________________mentioning
confidence: 99%
See 1 more Smart Citation
“…First, measurement across treatment sessions and maintenance probes were not kept constant (percentage vs. rate); second, although there were anecdotal reports of continued discard responses after intervention (use of toolbox, use of typical garbage receptacles, and putting items behind furniture), staff did not record the frequency of discard responses during maintenance probes; third, treatment fidelity was not directly assessed during the intervention; fourth, preference assessment procedures did not assess the impact of the stimuli on the frequency of pica as in contemporary competing stimuli assessments (Fisher et al 2004); and fifth, some methodological issues with the functional analysis could have been improved upon (e.g. additional sessions to demonstrate stability following the initially increasing trend and longer/more alone sessions may have been a more compelling demonstration of the nonsocially mediated function of pica).…”
Section: Limitationsmentioning
confidence: 99%
“…Following demonstration of the effectiveness of NCR across a multiple baseline design for all clients, systematic schedule thinning problem behaviors were maintained at near zero rates when NCR was provided on a fixed 5-min schedule. Fisher et al (2004) compared the effect of NCR plus extinction on a fixed schedule to extinction alone in treating the severe selfinjurious, aggressive, and destructive behavior in four individuals (aged 5, 7, 9, and 33) with significant intellectual disability. Their results indicate clear differences between treatment sessions that provided NCR in the form of social attention or tangibles from those where extinction alone was used.…”
Section: Noncontingent Reinforcementmentioning
confidence: 99%